International new ventures market expansion through collaborative entry modes: A study of the experience of Indian and British ICT firms. Issue 6 (12th November 2018) - Puthusserry, Pushyarag N.; Khan, Zaheer; Rodgers, Peter
Abstract : Purpose: The purpose of this paper is to examine the role that different collaborative entry modes play in how international new ventures (INVs) expand into international markets. Design/methodology/approach: The paper's arguments are based on the INVs and social network literatures. In order to investigate the entry modes adopted by British and Indian small and medium information and communication technology (ICT) firms into each other's markets, the paper outlines the results of qualitative semi-structured interviews with the key decision makers of ten British and ten Indian ICT firms. Findings: The findings contribute to the relatively under-researched area of how INVs enter foreign markets through collaborative entry mode. The findings suggest that INVs utilize both equity and non-equity modes of collaboration to expand their international operations. The findings also indicate that financial and non-financial resources always limit the market expansion and internationalization of such companies. Against this background, the INVs rely on building collaboration as one of the safest methods for foreign market expansion and successful internationalization. The collaborative entry mode is enhanced by entrepreneurs' prior experience, social ties and knowledge of the foreign market. Research limitations/implications: Set against the backdrop of an ever-increasing trend of internationalization of small and medium enterprises (SMEs), the paper offers important implications for understanding the conditions and factors behind the choice of collaborative and non-collaborative entry modes by INVs in particular and SMEs more broadly. Originality/value: The paper is one of the few studies that have examined the role of collaborative entry modes choice adopted by INVs from two of the largest economies – the UK and India.